Eziko: Feasts of power, gender roles and sacred spaces in Luke 22:14–20 - Penxa Matholeni, Nobuntu (HTS teologiese studies, 2025)
This article explored the significance of the upper room where Jesus invited his 12 disciples for a meal, focussing on the specific selection of both the men and the space. It investigated the potential contributions of the eziko [fireplace] in terms of inclusivity and decentralising the power dynamics of the Lord’s Supper. Asking how the eziko, as a site, can deconstruct gender biases and decentralise the power vested in the upper room. Using the indigenous storytelling methodology, nuancing the space of the eziko and juxtaposing it with the events described in Luke 22:14–20.Contribution: Among its key contributions, this article presents an interdisciplinary approach that integrates indigenous storytelling methodology with African indigenous knowledge systems, while also bridging theology with these cultural frameworks. This approach enhances academic discussions on contextual theology and promotes meaningful dialogue between Christian traditions and African indigenous religious practices.